2011
DOI: 10.1002/hep.24068
|View full text |Cite
|
Sign up to set email alerts
|

Inosine triphosphatase genetic variants are protective against anemia during antiviral therapy for HCV2/3 but do not decrease dose reductions of RBV or increase SVR

Abstract: Two functional variants in the inosine triphosphatase (ITPA) gene causing inosine triphos-phatase (ITPase) deficiency protect against ribavirin (RBV)-induced hemolytic anemia and the need for RBV dose reduction in patients with genotype 1 hepatitis C virus (HCV). No data are available for genotype 2/3 HCV. We evaluated the association between the casual ITPA variants and on-treatment anemia in a well-characterized cohort of genotype 2/3 patients treated with variable-duration pegylated interferon alfa-2b (PEG-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
60
0
1

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(69 citation statements)
references
References 13 publications
8
60
0
1
Order By: Relevance
“…As reported by recent studies (5,(12)(13)(14), Hb decrease is faster and more severe during the first 4 weeks of treatment in patients with the ITPA major allele (CC). The rapid decrease of Hb observed in major allele CC patients was associated with early reduction of RBV dosage, resulting in a lower total RBV administration.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…As reported by recent studies (5,(12)(13)(14), Hb decrease is faster and more severe during the first 4 weeks of treatment in patients with the ITPA major allele (CC). The rapid decrease of Hb observed in major allele CC patients was associated with early reduction of RBV dosage, resulting in a lower total RBV administration.…”
Section: Discussionmentioning
confidence: 63%
“…Recently, a genome-wide association study of determinants of treatmentrelated anemia in individuals with chronic HCV genotype 1 infection identified that genetic variants leading to ITPA deficiency protect against hemolytic anemia in HCV-infected patients receiving RBV (12). In the Caucasian population, there are two SNPs (rs7270101 and rs1127354) that are associated with ITPA enzyme activity (12,13), but one of these SNPs (rs7270101) is absent in Japanese patients (14). In this study, we confirmed the absence of rs7270101; the frequency of the rs1127354 major allele (CC) was 76.3% and that of the minor allele (CA and AA) was 23.7%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Because the RVR was reported as the most important predictor of SVR in HCV G2-infected patients, even when interleukin-28B variants were taken into consideration, 5,6 and ITPA variants were reported not to increase SVR in G2/3-infected patients with higher dose of RBV, 7 it is interesting to know whether the RVR is associated with ITPA variations and SVR in the present study of the NORDynamIC trial. 4 Particularly, because RVR is currently the most important factor for individualized therapy for G2/3-infected patients, the effect of the ITPA variants on determining the duration of Peg-IFN/RBV therapy for patients with or without RVR deserves to be explored.…”
Section: Variants Of the Inosine Triphosphate Pyrophosphatase Gene Anmentioning
confidence: 79%
“…Recent results by the same group analyzed patients infected with HCV genotypes 2 and 3, showing that ITPA variants are protective against treatment-related anemia, but are not related to the rate of SVR [134]. Among Japanese patients, only the SNP rs1127354 was strongly associated with the incidence and severity of RBV-induced HA [135,136].…”
Section: Epidemiology Research Internationalmentioning
confidence: 99%